Glutinous paddy land suitability under stress condition using multi-criteria AHP-GIS approach. - Hardanto, A.; Ardiansyah.; Setyawan, C.; Mandala, M.; Saparen, S.; Asrijal. (International Journal of Agricultural Technology, 2025)
The results indicated that the southern Java region is primarily classified as marginally suitable (S2), comprising 48.96% of the area (3,407.7 km²), followed by moderately suitable (S3) at 40.59% (2,825.3 km²). In contrast, the areas classified as not suitable (N) and highly suitable (S1) were relatively similar, comprising 5.55% (386.4 km²) and 4.90% (341.4 km²), respectively. Therefore, this region is presented a significant opportunity for cultivating glutinous rice, allowing for the productive use of less fertile land in Indonesia’s glutinous rice production.